Tinjaun Yuridis Terhadap Kesiapan Kewajiban Spin Off Bagi Unit UsahaSyariah (UUS) Menjadi Bank Umum Syariah (BUS) - Wiwin Muchtar Wiyono (Wijayakusuma Law Review, 2024)
Law Number 21 of 2008 concerning Sharia Banking in Article 68 paragraph 1 and Article 40 Article 40PBI No. 11/10/PBI/2009 mandates that every Sharia Business Unit (UUS) which is a sharia unit in aConventional Commercial Bank (BUK) to separate itself (spin-off). and it is explained that UUS is obligedto separate into BUS if the value of UUS assets has reached 50% (fifty percent) of the total asset value ofits parent BUK. The spin-off time is no later than 15 (fifteen) years from the enactment of the law, namely2023. The aim of this writing is to determine the impact of the spin-off on UUS by analyzing the solutionsthat can be offered. The research results show that it is necessary to review Law Number 21 of 2008concerning Sharia Banking by considering the financial condition of UUS. Apart from that, UUS whichhas carried out a spin-off by becoming a new BUS can optimize the use of Third Party Funds in the formof financing and other services. In order to encourage BUS growth, support from the government isneeded, such as providing tax incentives and simplifying regulations on capital participation. Apart fromthat, the new BUS needs to carry out various innovations by adding financing products and developingexisting products. This research aims to determine the readiness of the Spin Off obligation for UUS tobecome a BUS and the issue of readiness to fulfill the obligations of UUS to become a BUS in July 2023.Keywords: Spin-off Obligations, Sharia Business Units (UUS), Sharia Commercial Banks (BUS)